Rab'-e Rashidi: A Pioneering Educational and Medical Center in the Islamic World - Narges Tajik; Fatemeh Mollazadeh; Hamed Ahansazan; Mohammad Hossein Ayati (Traditional and Integrative Medicine)
Rab'-e Rashidi, a historical establishment, emerges as a paramount educational and medical institution in the Islamic world. Founded by Khwaja Rashiduddin Fazlullah Hamadani, this center encompassed a hospital, pharmacy, and provisions for patient families; while maintaining a strong focus on medical education. Historical texts reveal Rab'-e Rashidi's exceptional success during its time, positioning it as a leading educational and therapeutic hub that outperformed European universities in the field. This article delves into the profound impact of Iran's medical education system, with departments such as Dar al-Shafa (hospital), pharmacy, and early forms of drug processing laboratories, during the 8th century AH / 14th AD. This influence, which took root only a century after the peak of the Islamic civilization, left a lasting mark on both Islamic and Western territories. Notably, the presence of a university-hospital structure akin to the historic Jundishapur Scientific Center reflects the efficiency and unique educational approach that Iranians applied to medical education and doctor training. This study highlights Rab'-e Rashidi's pioneering role in shaping the landscape of medical education and its enduring legacy in the realm of healthcare and academia.